VD_FINDINFO Jug / 2025 / 170 vom 17. Dezember 2024 - VD Tribunal cantonal (2024)
VOLDROIT PÉNAL, CANNABIS, EXPULSIONDROIT PÉNAL, CONSTATATION DES FAITS | 139 ch. 1 CP, 144 CP, 186 CP, 66a al. 1 let. d CP